Synthesis, Crystal Structure, and Theoretical Calculation of the Cu(II) Complex With 1, 2-Benzisothiazolin-3-one. Issue 5 (3rd May 2016) - Li, Xia; Zhu, Guanhua; Dong, Lei; Ni, Chunhua; Yan, Xingchen; Yu, Liangmin
Abstract : A novel copper(II) complex [Cu2 (BIT)4 (DMF)2 ]2DMF (BIT = 1, 2-benzisothiazolin-3-one, DMF = N, N-dimethylformamide) was synthesized via standing diffusion method. The structure of crystal was characterized by elemental analysis, IR spectroscopy and single-crystal X-ray diffraction. The complex crystallizes in monoclinic C 2/ c space group and a = 30.850 (3) Å, b = 8.5534 (8) Å, c = 21.6491 (18) Å, β= 128.487 (2)°, V = 4.4716 (7) nm 3, Z = 4. The fluorescent properties of the complex was studied. Theoretical study of the complex was carried out by density functional theory B3LYP method using Gaussian 03 program. CCDC: 911350.